PEMBERDAYAAN MASYARAKAT NELAYAN PESISIR DESA LEATO TAHUN 2015-2020 - Mii, Dewi Agustiani; Pakaya, Sintia; Malae, Andri K. (Jambura History and Culture Journal, 2020)
The research objective was to reveal the Empowerment of the Psisir Fishermen Community in Leato Village in 2015-2020. In 2015 a single fish, tuna and deho processing factory was built in the village of Leato, but in 2019-2020 the factory was used only for freezing milkfish and shrimp. data from South Leato Village, the number of fishermen in South Leato is 442 people from 4 neighborhoods, and there are also those who work in other jobs such as employees, honorarium teachers, self-employment and other jobs. Even an employee before he started his job, he had time to work as a fisherman, this job has become a side livelihood. The condition of the houses in South Leato Village, especially the houses of the fishermen who are there, is quite good.